2018
DOI: 10.5301/tj.5000665
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel, oxaliplatin, 5-fluorouracil and leucovorin combination chemotherapy in patients with recurrent or metastatic gastric cancer

Abstract: Combination chemotherapy with POFL offers a new, active and safe approach to the treatment of recurrent or metastatic gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Our drug release properties are consistent with the fact that in combination chemotherapy, PTX is administered before long-term administration of 5-FU. 3,4,6,8 In addition, less than 20% of 5-FU and PTX were released from our (5-FU+PTX)@FHPL at 37 °C and pH 6.8, in contrast to the release of 80% of DOX and 100% of PTX within 12 h from L-HMSNs under the same conditions. 41 These results conrm that drug release from (5-FU+PTX)@FHPL is pH-and temperature-responsive.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Our drug release properties are consistent with the fact that in combination chemotherapy, PTX is administered before long-term administration of 5-FU. 3,4,6,8 In addition, less than 20% of 5-FU and PTX were released from our (5-FU+PTX)@FHPL at 37 °C and pH 6.8, in contrast to the release of 80% of DOX and 100% of PTX within 12 h from L-HMSNs under the same conditions. 41 These results conrm that drug release from (5-FU+PTX)@FHPL is pH-and temperature-responsive.…”
Section: Discussionmentioning
confidence: 87%
“…Recent studies have shown that paclitaxel (PTX) and 5-uorouracil (5-FU) can be synergistically used to treat breast and gastric cancer. [3][4][5][6][7][8] PTX is a hydrophobic drug commonly used for the treatment of breast, ovarian, and lung cancers. 9 However, its extremely poor water solubility requires the use of special solubilizers, such as Cremophor EL and absolute ethanol (1 : 1), 10 which lead to allergic reactions, signicantly limiting the application of PTX in cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTX and 5-FU are attractive options because of their distinct mechanisms of action, nonoverlapping toxicity, and potential synergy. Many studies have illustrated that PTX combined with 5-FU shows efficacy and tolerability for the treatment of certain solid tumors, particularly primary/metastatic breast carcinoma, drug-refractory ovarian cancers, and advanced/recurrent/metastatic gastric cancer [ 7 , 8 , 9 , 10 , 11 ]. Patients in these studies were treated with different dosages or routes: PTX was administered weekly, biweekly, or triweekly, while 5-FU was administered by bolus injection or continuous infusion with or without other chemotherapeutics in chemotherapy or a neoadjuvant or adjuvant setting [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Paclitaxel is a first-line chemotherapeutic agent for solid tumors, but its use has been confounded by poor solubility, toxicity and the emergence of resistance during therapy (4,5). In order to improve efficacy and to decrease the emergence of resistance, clinicians combine paclitaxel with cisplatin and other antineoplastic drugs (6,7). as nanotechnology has progressed, multiple types of paclitaxel nanoparticles (nPs) have been developed to modulate drug release, promote drug encapsulation, improve bioavailability and target cancer cells by using frame materials of polyethylene glycol, polylactic acid, polyglycolin acid or liposomes (8).…”
Section: Introductionmentioning
confidence: 99%